The Effects of Accounting Knowledge and Context on the Omission of Opportunity Costs in Resource Allocation Decisions. - Vera-Muñoz, Sandra C. (The Accounting Review, 1998)
Abstract Economic theory stresses that opportunity costs are relevant to resource allocation decisions, while prior empirical accounting research finds that decision makers tend to ignore or underweight opportunity cost information. This study examines whether accounting knowledge is associated with a decision maker's tendency to ignore opportunity costs in business decisions. The experiment's results indicate that the number of opportunity costs ignored by subjects in a business resource allocation decision is greater for subjects with high-accounting knowledge than for subjects with low-accounting knowledge. The experiment also indicates that subjects with high- accounting knowledge ignore a greater number of opportunity costs when the decision is posed in a business context than when it is posed in a personal context.